Factors associated with anaemia and iron deficiency among women of reproductive age in Northeast Thailand: a cross-sectional study - Jutatip Jamnok; Kanokwan Sanchaisuriya; Pattara Sanchaisuriya; Goonnapa Fucharoen; Supan Fucharoen; Faruk Ahmed (BMC, 2020)
Abstract Background Anaemia and iron deficiency (ID) affect women of reproductive age globally and considered to be a major public health problem in developing countries. This study determines the prevalence of anaemia and ID among women of reproductive age in urban northeast Thailand and examined the relative contribution of various risk factors to anaemia and ID in this population. Methods Three hundred ninety-nine non-pregnant women, aged 18-45 years, from three universities in northeast Thailand participated in this cross-sectional study. Selected socio-demographic, history of blood loss, usual consumption of red meat and tea/coffee, and anthropometric data were collected. Complete blood count including haemoglobin (Hb) concentration, serum ferritin (SF), C-reactive protein (CRP), and thalassemia were determined. Multiple logistic regressions were applied to identify the risk factors of anaemia and ID. Results Overall, 370 participants were included for data analyses after excluding women with severe/intermedia thalassemia diseases and/or those with positive serum CRP. The prevalence of anaemia, ID, and iron deficiency anaemia (IDA) were 28.4, 28.4, and 13.2%, respectively. Women with thalassemia had a higher prevalence of anaemia but a lower prevalence of ID than the women without thalassemia. By multiple regression analysis, ID [adjusted OR (AOR) = 4.9, 95% CI = 2.8-8.3], two α-gene defects (AOR = 8.0, 95% CI = 3.0-21.3) and homozygous Hb E (AOR = 8.5, 95% CI = 3.0-24.3) were identified as the potential risk factors of anaemia. Further, the odds of ID were significantly higher among women who donated blood within the past 3 months (AOR = 6.7, 95% CI = 2.8-16.3), and had moderate to a high amount of blood loss during menstruation (AOR = 2.2, 95% CI = 1.3-3.9). Conclusion This study found a relatively high but differential prevalence of anaemia and ID among women of reproductive age with or without thalassemia. Only homozygous Hb E and two α-gene defects of thalassemia types and ID were the main factors contributing to anaemia. Recent blood donation, and moderate to a high amount of blood loss during menstruation were potential risk factors of ID in this population.